Implementation of Independent Learning Curriculum Management in Improving the Quality of Education at SD Negeri 115 Palembang - Yus Meri Yanti; Alhadi Yan Putra; Pahlawan Pahlawan (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to describe and analyze the Merdeka Learning Curriculum to understand the supporting and inhibiting factors in the implementation of the Merdeka Learning Curriculum to improve the quality of education at SD Negeri 115 Palembang. This research uses a qualitative method with a field research approach through data and data sources. Data collection techniques include observation, interviews, and documentation. The research findings indicate that the implementation of the Independent Learning Curriculum management in improving the quality of education at SD Negeri 115 Palembang can be summarized through several stages: planning, organizing, actuating, and evaluating. There are two factors that influence the improvement of educational quality, namely supporting factors, which include school leadership, coordination, cooperation, and teachers' skills in managing the classroom. The inhibiting factors include facilities and infrastructure, education funding, and the still limited quality of teachers or educators. In improving the quality of education at SD Negeri 115 Palembang, it can be concluded that the implementation of management has not yet reached an optimal level. However, its success is notable, even though it is not yet widespread due to several inhibiting factors. To anticipate the inhibiting factors, it is necessary to improve facilities and infrastructure, which require support from the school principal and guidance from relevant parties, such as socialization and training from the Education Department or external trainers, so that the skills of teachers and educational staff become more professional and developed.